Therapeutic Effect of Levodopa/Carbidopa/Entacapone on Sleep Disturbance in Patients with Parkinson’s Disease - Park, Kye Won (J Mov Disord, 2020)
OBJECTIVE: To investigate the efficacy of levodopa/carbidopa/entacapone (LCE) at bedtime for treating sleep disturbance in patients with Parkinson’s disease (PD) with motor fluctuations. METHODS: Participants included 128 PD patients with motor fluctuations. All patients were assessed for motor, nonmotor, and sleep-specific symptoms using the United Parkinson’s Disease Rating Scale (UPDRS), the Korean version of the Nonmotor Symptom Scale, the Parkinson’s Disease Sleep Scale (PDSS), the Epworth Sleepiness Scale, and the Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire (RBDSQ). We compared the baseline characteristics of patients with sleep disturbance (PDSS score < 120) and those without sleep disturbance (PDSS score ≥ 120). Thirty-nine patients with sleep disturbance who agreed to take LCE at bedtime completed 3-month follow-ups. We analyzed changes in the scores of motor, nonmotor, and sleep symptom scales over the 3 months. RESULTS: PD patients with sleep disturbance were at more advanced disease stages and had more severe motor, nonmotor, and sleep symptoms than those without sleep disturbance. Patients who took LCE at night showed improvements in motor (UPDRS part III, p = 0.007) and sleep symptoms (total PDSS, p < 0.001). Sleep features that benefitted from LCE included not only nocturnal motor components but also insomnia (PDSS items 2 and 3, p = 0.005 and p < 0.001) and rapid eye movement behavior disorder (PDSS item 6, p = 0.002; and RBDSQ, p < 0.001). CONCLUSION: The use of LCE at bedtime may be a useful treatment for sleep disturbance in advanced PD patients with motor fluctuations.